2015
DOI: 10.1130/g36570.1
|View full text |Cite
|
Sign up to set email alerts
|

Human impact overwhelms long-term climate control of weathering and erosion in southwest China

Abstract: International audienceDuring the Holocene there has been a gradual increase in the influence of humans on Earth systems. High-resolution sedimentary records can help us to assess how erosion and weathering have evolved in response to recent climatic and anthropogenic disturbances. Here we present data from a high-resolution (∼75 cm/k.y.) sedimentary archive from the South China Sea. Provenance data indicate that the sediment was derived from the Red River, and can be used to reconstruct the erosion and/or weat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 26 publications
6
82
1
Order By: Relevance
“…Such an attempt has been recently made by Wan et al . [] and Lupker et al . [] using the core data from the continental slope of the South China Sea and the Bengal Fan respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Such an attempt has been recently made by Wan et al . [] and Lupker et al . [] using the core data from the continental slope of the South China Sea and the Bengal Fan respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sediments in the delta region and the margin of the South China Sea have been extensively studied to reconstruct the history of local delta formation, the evolution of the South China Sea, and their relationships with the Asian monsoon and tectonic uplift of the Tibetan Plateau [ Li et al ., ; Wan et al ., ]. In particular, several studies have investigated the magnetic properties of sediments from the South China Sea in order to reconstruct paleoenvironmental changes [ Kissel et al ., ; Ouyang et al ., ; Wang et al ., ].…”
Section: Introductionmentioning
confidence: 98%
“…The accumulations of these sediments in deltas and continental margins contain valuable information about geological history, climate changes, and human activity in the river catchment and thus they have been extensively studied to reconstruct environmental changes on different time scales [e.g., Colin et al ., ; Kissel et al ., ; Bianchi and Allison , ; Wan et al ., ]. Geochemical and mineralogical methods are conventionally used to characterize sediments derived from these large rivers [e.g., Clift et al ., ; Wan et al ., ]. A number of indicators have been developed [e.g., Clift et al ., , and references therein], such as the conservative Al/Ti ratio for sediment provenance [ Young and Nesbitt , ], and the chemical index of alteration (CIA) [ Nesbitt and Young , ] for climate changes.…”
Section: Introductionmentioning
confidence: 99%
“…Provenance estimation based on REE indicates that both the Red and Pearl Rivers contribute almost equally to Site 38, which is close to PC338 at a water depth of 1,160 m (Liu et al, ). Nd‐Sr isotope results indicate that the Red River is the primary source for core 337PC (Figure a) at a water depth of 516 m (Wan et al, ). REE comparisons demonstrate that the Pearl and southwestern Taiwan Rivers are the main sources for core X2 (Figure a) close to Hainan Island at 77 m water depth (Xu et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Cores ODP1144 (Hu et al, ), STD111 (Yang et al, ), MD12–3432 (Chen et al, ), ODP1146 (Kissel et al, ), Qd34 (Yang et al, ), PC24 (Ouyang et al, ), PC83 (Yang et al, ), and PC111 (Yang et al, ) in the northern SCS have also been studied magnetically. Cores STAT22 (Cui et al, ), X2 (Xu et al, ), 337PC (Wan et al, ), and Site 38 (Liu et al, ) were used for provenance studies. Huguangyan Maar Lake (HML; Wang et al, ), Dongge Cave (Dykoski et al, ), Hulu Cave (Wang et al, ), and KNG5 (Huang et al, ) have yielded high‐resolution paleoclimate records and are indicated on the map.…”
Section: Introductionmentioning
confidence: 99%